Poetics in intervention: pulsatile existence in the urban space - Boemer, Otavio Fabro (Farol, 2026)
This article analyzes the historical changes and influences on the operational practices of interventionists who emerge from the cracks of the urban habitat, based on the urgency of expressive survival. By investigating the mode of operation — graffiti — in the Brazilian context as a resilient everyday tactic converted into an aesthetic proposition of occupation, its utopia of experiencing the city as a revitalized work of art is articulated. From the new individual bodies that emerged in the illegal intervention as a pulsating collective body in expressive (re)existence—inhabiting, its anomalous aesthetic, consolidated and co-opted, will also see the emergence of mere prêt-à-porter identities. However, it is perhaps through the practice of composting the urban substrate—revitalized within a social collective that refuses domestication—that its subversive power will withstand the risk of becoming merely another prop in the urban shop window.
Keywords: contemporary art; urban intervention; pulsating body; expressive (re)existence; graffiti